Exploring and Modeling the Spatial Variability of Soil Erosion in Tana Basin, Northwestern Ethiopia - Derege Tsegaye Meshesha; Anteneh Wubet Belay; Gizachew Ayalew Tiruneh; Enyew Adgo; Tiringo Yilak Alemayehu; M. Chandrakala; José Miguel Reichert (Applied and Environmental Soil Science)
Soil degradation exacerbates the depletion of soil resources and poses a threat to agricultural productivity and environmental sustainability. To address this issue, initiatives focusing on soil and water conservation (SWC) were carried out in the Tana Basin watershed located in Ethiopia. However, their spatial distribution, status, and effects of SWC activities on soil erosion were not evaluated in the entire study watershed. Thus, a revised universal soil loss equation (RUSLE) was adopted to identify soil erosion prone areas and evaluate the effect of SWC activities on soil erosion in Ethiopia. The finding shows the average soil loss of the catchment is 18.65 t/ha/year (moderate), and the detached and transported soil is 7934 tons/year. By implementing bunds in croplands and restricting grazing in degraded bushlands, it is feasible to reduce current soil erosion by 47% of the overall soil loss. The catchment area shows varying degrees of soil erosion, with a minimal rate in some areas, while others experience slight, moderate, severe, and very severe rates of soil loss, which make up 15.5%, 13.3%, 12.8%, and 10.9%, respectively. The prediction efficiency of the RUSLE using ground-measured soil erosion data results (R2 = 0.90) revealed reliability. Consequently, the initial situation (soil bund and enclosure) results in a 47% reduction in erosion, the second situation involves increased expenses in materials and labor by 53% compared to the first scenario, and the third situation converts all deteriorated bushlands into forest land by 10%. Therefore, recommended SWC practices should be adopted in the Kecha and similar watersheds to minimize soil erosion and sustain soil productivity.